A plug-and-play aptamer diagnostic platform based on linear dichroism spectroscopy - Little, Haydn A.; Ali, Aysha; Carter, Jake G.; Hicks, Matthew R.; Dafforn, Timothy R.; Tucker, James H. R. (Frontiers in Chemistry, 2023)
A plug-and-play sandwich assay platform for the aptamer-based detection of molecular targets using linear dichroism (LD) spectroscopy as a read-out method has been demonstrated. A 21-mer DNA strand comprising the plug-and-play linker was bioconjugated onto the backbone of the filamentous bacteriophage M13, which gives a strong LD signal due to its ready alignment in linear flow. Extended DNA strands containing aptamer sequences that bind the protein thrombin, TBA and HD22, were then bound to the plug-and-play linker strand via complementary base pairing to generate aptamer-functionalised M13 bacteriophages. The secondary structure of the extended aptameric sequences required to bind to thrombin was checked using circular dichroism spectroscopy, with the binding confirmed using fluorescence anisotropy measurements. LD studies revealed that this sandwich sensor design is very effective at detecting thrombin down to pM levels, indicating the potential of this plug-and-play assay system as a new label-free homogenous detection system based on aptamer recognition.